Hypericum japonicum Thunb. ex Murray: Phytochemistry, Pharmacology, Quality Control and Pharmacokinetics of an Important Herbal Medicine - Liu, Lin-Sheng (Molecules, 2014)
Hypericum japonicum Thunb. ex Murray is mainly distributed throughout Asia, Oceania and North America and is used as an important herbal medicine. H. japonicum contains many valuable secondary metabolites, such as flavonoids, phloroglucinols and xanthones and has hepatoprotective, anti-tumor, antibacterial, antiviral, and antioxidant activities and effects on the cardiovascular system and immunity. Coupled with phytochemical and pharmacological research, a series of analytical methods have been developed to evaluate the quality of H. japonicum based on its bioactive components. A pharmacokinetics study involved the absorption of two main flavonoids of H. japonicum in rats. This review aims to present an up-to-date and comprehensive overview of the phytochemistry, pharmacology, quality control and pharmacokinetics of H. japonicum, which should be useful for the greater development of H. japonicum, especially in the development of new drugs and therapeutics for various diseases.